Free: two years, six lives, and the long journey home - Kessler, Lauren (Sourcebooks, 2022)
"95 percent of the men and women who go to prison are eventually released. But then what? A gripping work of immersion reporting for readers of Evicted and Maid, Free shines a spotlight on the rollercoaster of re-entry: the exuberance of freedom, the rules and regulations that make you feel like you're still in prison, the often dispiriting work of looking for employment and housing, and more. Veteran reporter Lauren Kessler follows six individuals whose diverse stories paint a portrait of the search for redemption that many former inmates face as they fight to rebuild their lives"--